Using e-wallet for business process development: challenges and prospects in Malaysia - Alam, Md Mahmudul; Awawdeh, Ala Eldin; Muhamad, Azim Izzuddin (Emerald Group Publishing Limited, 2021)
Purpose – This study aims to explore the challenges and prospects of using e-wallets in Malaysia, and what it means for businesses and customers. Suggested here are strategies to leverage the strengths and opportunities as well as overcome the weaknesses and threats. Suggested here are strategies to leverage the strengths and opportunities as well as overcome the weaknesses and threats. Design/methodology/approach – This study analyses the e-wallet phenomenon using a SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis to assess Malaysian business development. It is supported with findings from the literature and secondary data. The relevant secondary data were collected from Bank Negara Malaysia and the World Bank. Findings – This study shows that e-wallets in Malaysia have still not achieved their purpose but there is huge potential to do so. The SWOT analysis identified several strengths (e.g. financial incorporation, easy to access, protection and safety, simple for other accounts to connect to, product and consumer service management, quick to implement/administer), weaknesses (e.g. lack of infrastructure and the “tapping” of devices already cornered by the mobile phone market, opportunities (e.g. eliminating fraud, better customer service, promotion/ loyalty that can be built into customer experience) and threats (e.g. attacks from viruses, frequent inquiries whether multiple wallets can be used by clients, the concerns of reckless spending behaviour of the e-wallet users). Research limitations/implications – This study is crucial for assessing the current situation and the prospects of e-wallets in Malaysia. This study also offers significant insights for policymakers and e-wallet service providers to develop appropriate strategies to enhance e-wallet services in Malaysia. Originality/value –This paper is the first of its kind to integrate a SWOT analysis and the rapid development of the e-wallet market in Malaysia. Hence, the findings could broaden our knowledge on the fintech industry and enable firms to participate in the e-wallet market.